2006
DOI: 10.1021/la062082w
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Drop Size and Polydispersity Using Chemically Patterned Surfaces

Abstract: We explore numerically the feasibility of using chemical patterning to control the size and polydispersity of micron-scale drops. The simulations suggest that it is possible to sort drops by size or wetting properties by using an array of hydrophilic stripes of different widths. We also demonstrate that monodisperse drops can be generated by exploiting the pinning of a drop on a hydrophilic stripe. Our results follow from using a lattice Boltzmann algorithm to solve the hydrodynamic equations of motion of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 35 publications
(108 reference statements)
3
32
0
Order By: Relevance
“…* huanghb@ustc.edu.cn Due to mesoscopic property, the above multiphase LBMs have some advantages over conventional methods for multiphase flows [28][29][30][31][32]. Hence, they are also used to model contact line dynamics [29][30][31][32]. With the Shan-Chen model, Kang et al studied 2D droplets sliding on smooth walls and investigated effects of the wettability, Bond number, droplet size, and density and viscosity ratios of two phases [14].…”
Section: Introductionmentioning
confidence: 99%
“…* huanghb@ustc.edu.cn Due to mesoscopic property, the above multiphase LBMs have some advantages over conventional methods for multiphase flows [28][29][30][31][32]. Hence, they are also used to model contact line dynamics [29][30][31][32]. With the Shan-Chen model, Kang et al studied 2D droplets sliding on smooth walls and investigated effects of the wettability, Bond number, droplet size, and density and viscosity ratios of two phases [14].…”
Section: Introductionmentioning
confidence: 99%
“…Regular arrays of chemical patches [4,5,6] and posts [7,8,9,10] of different shapes and sizes are regularly fabricated and several authors [11,12,13] have even shown the possibilities of manufacturing multi-scale surface patterns. Recently such patterning has been used to control the movement of drops [16,17] and to attempt to enhance flow in microchannels [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In the first [55], we show how a (relatively) hydrophobic grid can be used to alleviate mottle [56] in ink-jet printing. In the second example, we demonstrate that chemical patterning can be used to control drop size and polydispersity [57]. Figure 11.8 compares experiments and simulations of drops on a chemically patterned substrate.…”
Section: Chemical Patterningmentioning
confidence: 91%